The Influence of Good Corporate Governance on Banking Financial Performance Period 2016-2020 - Rendra Ani Asmara; Widi Hariyanti; Agus Endrianto Suseno3 (Profesional Muda Cendekia Publishing, 2022)
Good Corporate Governance (GCG) is a company management and control system to maintain a balance between the authority and responsibility of the company. The implementation of GCG in the company is a concept used to maintain consistency and public trust in the community. Therefore, the presence of GCG has now become an essential need that goes beyond the needs of investors and corporate governance. This study was conducted to determine the effect of the implementation of GCG on financial performance. The research sample is banks listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period with a sampling target. This research uses descriptive quantitative method and simple regression method. The variables of Corporate Governance Disclosure Index (CGDI), Return on Assets (ROA) and Return on Equity (ROE) were analyzed using SPSS 21. The results showed that Good Corporate Governance (GCG) had a significant positive effect on Return on Assets (ROA) and Return on Equity (ROE) at banks listed on the Indonesia Stock Exchange for the 2016-2020 period.